TINDAK TUTUR ILOKUSI PESERTA DISKUSI DALAM ACARA ILC (INDONESIA LAWYERS CLUB) DI STASIUN TELEVISI TV ONE EDISI KASUS DUGAAN KORUPSI SETYA NOVANTO - Ayuri, Septie Miranda; Agustina, Agustina; Juita, Novia (Jurnal Bahasa dan Sastra, 2018)
This research is about the strategy of telling in the event of ILC (Indonesia Lawyers Club) in TV ONE which is said by the discussion participants on the topic about "Setya Novanto". This research type is qualitative research with descriptive method. First, the type of speech acts of illocution most commonly found in the speech of the participants of the event discussion (Indonesia Lawyers Club) is an expressive act of 'criticizing' that is as much as 207 speeches. Second, the strategy of telling the story of the illocution spoken by the discussion participant in the event (Indonesia Lawyers Club), is to have the same amount of use of the strategy type that is in using the strategy of telling frankly with the positive politeness gesture and speaking vaguely, vague that is equally as much as 89 speech. Thirdly, the context of the use of the strategies described in the act of speech of illocution is most often found in the context of speech is the same speaker with speakers using the type of strategy speak with positive politeness gestures in expressive (criticizing) illustrated speech acts. Fourth, the impact of language proficiency on the use of vague speech strategies (BSS) is more likely to be used by public officials in the event (Indonesia Lawyers Club) as much as 41 the number of speeches in the context of the speech utterance as position with the speaker.Â Keywords: Tindak tutur ilokusi, peserta diskusi, ILC (Indonesia Lawyers Club),Â Setya Novanto